LAW ENFORCEMENT AGAINST THE CRIME OF TRAFFICKING IN PROTECTED ANIMALS (STUDY AT THE NORTH SUMATRA POLICE) - Yunita Restu Widiya; Taufik Siregar; M. Citra Ramadhan (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The illegal trade of protected wildlife constitutes a serious form of environmental crime that continues to evolve, particularly through the use of social media as a platform for illicit transactions. This study aims to examine the modus operandi of protected wildlife trafficking conducted via social media, analyze law enforcement efforts undertaken by the North Sumatra Regional Police, and identify the obstacles faced in enforcing the law. This research employs a normative legal research method using statutory and conceptual approaches, supported by an analysis of primary, secondary, and tertiary legal materials. The findings indicate that wildlife trafficking has shifted toward digitally based and covert practices, posing significant challenges to conventional law enforcement mechanisms. Although the North Sumatra Regional Police have implemented both penal and non-penal measures, their effectiveness remains limited due to resource constraints, difficulties in digital evidence gathering, and low public legal awareness. Therefore, strengthening institutional capacity, enhancing inter-agency cooperation, and fostering a supportive legal culture are essential to optimizing the enforcement of laws protecting wildlife and ensuring ecological sustainability.